Cervical ectopic pregnancy: ultrasound diagnosis and conservative management - Chauhan, Nidhi; Goyal, Priyanka; Lal, Arjun; Chhatwal, Jashan; Shamim, Saba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
An ectopic pregnancy is one in which the fertilized ovum is implanted and develops outside the normal endometrial cavity. Cervical ectopic pregnancy is a rare form of ectopic pregnancy and can be defined as implantation of blastocyst in the endocervix, below the internal os; representing less than 1 % of all ectopic pregnancies. Ultrasound diagnosis of this abnormal pregnancy was first described by Raskin (1978); thus early diagnosis in either weakly or non-symptomatic women in the first trimester is done; allowing conservative management. A 35 year old female, gravida 4 with living 1 issue and 2 abortions presented with a history of continuous bleeding per vaginum for last 1.5 months. Outside ultrasound depicted single live fetus of 7 weeks in cervical canal. She had a history of undergoing medical termination of pregnancy by surgical procedure of dilatation and evacuation at private hospital for completion of abortion. There was a history of excessive bleeding post procedure and 2 units of blood transfusion; referred in anaemic state to our institute with pack in situ. Pack was removed after 24 hours and managed conservatively. On general examination tachycardia present, BP was normal and patient was haemodynamically stable. On palpation abdomen was soft, non-tender and no organomegaly noticed. Urine pregnancy test was positive, serum βHCG levels were raised, USG depicted heterogeneous collection in cervix. Injection methotrenate (1mg/Kg body wt.) given. βhCG repeated after 7 days; levels decreased significantly. Patient was improved symptomatically and bleeding stopped. Cervical pregnancy is a rare condition, if not diagnosed and treated early during the course of pregnancy can have hazardous complications. Thus early diagnosis and management is necessary for preserving patient’s fertility without significant complications.